Broadcast Territories - Sam Jacob (Oz, 2012)
On November 16, 1974, a radio message was broadcast from the Arecibo radio telescope in Puerto Rico towards the globular star cluster M13 some 25,000 light years away, a patch of the cosmos considered the most likely to be home to alien civilizations.